Angiotensin Receptor Blockers for COVID-19: Pathophysiological and Pharmacological Considerations About Ongoing and Future Prospective Clinical Trials - Rothlin, Rodolfo Pedro; Duarte, Mariano; Pelorosso, Facundo Germán; Nicolosi, Liliana; Salgado, M. Victoria; Vetulli, Héctor Miguel; Spitzer, Eduardo (Frontiers in Pharmacology, 2021)
COVID-19 pandemic demands a swift response to find therapeutic tools that effectively reduce morbidity and mortality. Despite initial fears, evidence from retrospective observational studies supports the inhibition of the renin-angiotensin system as an emerging pathway to delay or moderate angiotensin II-driven lung inflammation. This has triggered several prospective clinical trials. In this commentary we provide an overview and analysis of current ongoing clinical trials aimed at evaluating the therapeutic efficacy of angiotensin receptor blocker (ARB) use in COVID-19. The relevance of the results of these trials will have to be interpreted depending on the stage and severity of the disease and in light of the start time of their prescription related to the time of diagnosis of COVID-19 as well as the administered doses.